MANAGEMENT INFORMATION SYSTEMS: CHARACTERISTICS AND ROLE IN MODERN ORGANIZATIONAL TRANSFORMATION - Fila, Arfania Zuhru; Mursid, Mansur Chadi; Caniago, Siti Aminah (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Management Information Systems (MIS) are a crucial element in supporting the transformation of modern organizations in the digital era. This article discusses the main characteristics of MIS, which consist of people, data, hardware, software, and business procedures. These five elements interact in an integrated manner to support operational efficiency and more effective decision-making. As technologies such as artificial intelligence (AI), big data, cloud computing, and the Internet of Things (IoT) develop, MIS has evolved into an intelligent system that is adaptive and responsive to market dynamics. This transformation allows organizations to manage data in real time, accelerate innovation, and increase competitiveness. However, the implementation of MIS is not free from various challenges, such as high investment costs, resistance to change from employees, and complex data security issues. Therefore, organizational support through the development of digital skills, strengthening technology infrastructure, and effective change management strategies is crucial to the success of MIS implementation. Through a comprehensive literature review, this article emphasizes that MIS is not only an operational tool but also a key driver in building a more innovative, adaptive, and competitive organization.